The Pennsylvania Railroad : the long decline, 1933-1968 - Churella, Albert J., 1964- (Indiana University Press, 2024)
"The final volume of Albert Churella's monumental history of the Pennsylvania Railroad, this book begins with the height of the era of steam locomotives and follows the railroad through the turn of the century until its ultimate collapse and demise in 1968"-- Provided by publisher.
Includes index.
Keywords: Pennsylvania Railroad -- History.; Railroads -- Pennsylvania -- History.; TRANSPORTATION / Railroads / History.; TRAVEL / Food, Lodging & Transportation / Rail Travel.; Electronic books.